The future of energy harvesting: a brief review of MXenes-based triboelectric nanogenerators - Mohan, Raja; Ali, Fathilah (Wiley, 2023)
Triboelectric nanogenerators (TENGs) have shown immense potential as self-powering devices for energy harvesting, electronics, and self-powered sensing devices. However, the performance of TENGs largely depends on the materials used, therefore, it is crucial to select appropriate materials. While dielectric polymers, metals, and inorganic materials have been commonly employed as active materials for TENGs, there is a need to explore new materials that offer improved performance. One promising material is two-dimensional MXenes, which have shown exciting potential in various applications, including wearable sensors and electrochemical energy storage. For this reason, further research is needed to fully evaluate the performance of MXenes-based TENGs and to determine their suitability for practical applications. This review emphasizes the significance of material selection in order to optimize the performance of triboelectric nanogenerators (TENGs). Here, the mechanism of TENGs is clearly explained for devices that convert mechanical energy into electric energy. The concept of the triboelectric effect is also described, which generates charge density on material surfaces, along with various types of TENG working modes. The selection of materials is thoroughly discussed, highlighting the growing interest in polymeric and biopolymeric materials, as well as functionalized and inorganic triboelectric materials. Also, exploration of materials that can enhance the output of TENGs, such as chemical modification techniques and the utilization of 2D materials like graphene and MXenes to improve triboelectricity is also included. The synthesis methods and techniques for MXenes are explored in detail. Furthermore, the performance of MXenes-based TENGs for energy harvesting and self-powered sensing is evaluated, and their potential applications in wearable devices are assessed. The study concludes by providing recommendations for future research on MXenes-based TENGs and their applications in wearable devices.